Islam Santuy in Cyberspace: Existence, Contestation and Resistance - Mukarromah, Mukarromah (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2024)
The Indonesian millennial generation tends to be influenced by extreme Islamist movements on social media, which challenge the idea of moderate Islam. This research aims to examine the message and implications of the “NU Garis Lucu” da’wah in the efforts of existence, resistance, and contestation with the Islamism Movement in cyberspace. This research method uses qualitative analysis using Roland Barthes’ semiotics and Norman Fairclough’s Critical Discourse Analysis. The results of the study concluded that the message of the “NU Garis Lucu” da’wah in relation to contestation and resistance with the Islamism Movement is carried out through jokes/humor in each of its posts. The implications of the “NU Garis Lucu” da’wah message in carrying out resistance and contestation against the Islamism Movement in the world are through these posts, which ultimately give birth to Islam tawasuth, Islam tasamuh, and humanism. So that it can provide an understanding of religious moderation with a humorous approach through the “Islam Santuy” and “NU Garis Lucu” Movements, which are effective in reaching the millennial generation and countering extremist narratives on social media.